Regional pattern of smoking in Croatia - Samardžić, Senka (Array, 2009)
Summary: The aim of this paper was to investigate the regional smoking pattern in Croatia. The data from the Croatian Adult Health Survey from 2003 were used for the study (N=9,070). The results of this study suggest that the prevalence of smoking among men was the highest in the Eastern parts of the country, followed by the Mountainous region. In contrast, the prevalence of smoking among women was the highest in City of Zagreb. The results support the strong regional pattern, with more pronounced differences in women (those from the City of Zagreb had more than twice higher prevalence than those from the Northern parts of the country). Smoking is still relatively highly prevalent in Croatian adult population (24–33% in men, and between 10 and 21% in women, depend on region). This suggesting that preventive actions and public health interventions are needed to reduce the smoking prevalence and thus improve the population health